Pengembangan Video Dokumenter Berbasis Local Content Alat Musik Tradisional Pada Materi Gelombang Bunyi - Hisbulloh Als Mustofa; Gunawan Gunawan; Kosim Kosim; Sutrio Sutrio (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
Changes in the learning system during the COVID-19 pandemic require innovation in learning, innovation in the development of video learning media can be a solution, including documentary videos. The documentary video itself is one of the learning media that contains events and phenomena of everyday life that are close to students. Integrating documentary videos with the local content of traditional musical instruments to explain sound wave material can significantly assist students in understanding the material. This study aims to develop a local-based documentary video content of traditional musical instruments on sound waves. This study uses the Research and Development method with a 4D model (Define, Design, Develop, and Disseminate) developed by Thiagarajan by making documentary videos through the pre-production, production, and post-production processes. The development process started from the draft of the learning video and was revised twice based on suggestions and input from 3 expert validators and 3 practitioner validators then a commentary through suggestions from respondents. Then the documentary video was obtained as the final learning media with a validity percentage of 93% based on expert judgment and 89% based on respondent's assessment. So it can be said that a final documentary video has been produced which is very feasible for use in learning.